PERBANDINGAN TINGKAT KECEMASAN PERAWAT DALAM PENANGANAN PASIEN COVID-19 DI UNIT GAWAT DARURAT, ISOLASI WINGS, DAN ISOLASI UTAMA - Upayanti, Kadek Febri Dwi; Krisnawati, Komang Menik Sri; Yanti, Ni Putu Emy Darma (Coping: Community of Publishing in Nursing; Vol 9 No 5 (2021): Oktober 2021DO - 10.24843/coping.2021.v09.i05.p14, 2021)
Coronavirus  Diseases  2019   (Covid-19)  is  a  major  health  problem  in  the  world nowadays. Covid-19 has negative impacts on the nurse’s mental health, one of  them is anxiety. Continuous exposure of anxiety has negative impacts on the physical, psychological, and work performance of nurses. This study aimed to nurses’ anxiety levels in handling Covid-19  patients  at  Emergency  Room,  Wings  Isolation,  and  Main  Isolation  in  Bangli General Hospital. This study was a quantitative study with comparative analytical study. This research used a cross-sectional study design. The sample size in this study was 43 nurse selected using random sampling technique. The instrument that used in this study was ZSAR- S  (Zung  Self  Anxiety  Rating-Scale).  The   Kruskal  Wallis   comparative test  showed  a significant result on the level of anxiety variable with p- value = 0.009 (p <0.05), which means there differences of nurses anxiety level at Emergency Room, Wings Isolation, and Main Isolation. The results also showed that 31.25% of nurses in the Wings Isolation Room experienced mild anxiety. In conclusion,   nurses who work in the Wings Isolation Room experienced higher anxiety compared to nurses who work in the Emergency Room and Main Isolation Room.